A multiport DC-to-DC converter-driven inductive wireless charging system for EVs with integrated photovoltaic and energy storage systems - Aganti Mahesh; Bharatiraja Chokkalingam; C. Santhakumar; K. Sathiyasekar; Sanjeevikumar Padmanaban (Scientific Reports)
Abstract This paper introduces an innovative three-port DC–DC converter (TPC)-based wireless charging system (WCS) that seamlessly integrates photovoltaic (PV) and an energy storage system (ESS). The proposed system leverages the advantages of an isolated topology, enhancing safety, reducing electromagnetic interference, and enabling flexible power management. The regulation of input ports from PV and ESS (battery) is achieved through a pulse width modulation switching scheme, ensuring stable voltage across the WCS port. The isolated design also enables bidirectional power flow at the ESS port under specified conditions, facilitated by auxiliary switches. The WCS port incorporates series–series and LCC-S compensation, ensuring efficient power transfer under various misalignment and load conditions. The proposed system is validated through simulation using MATLAB and Ansys Maxwell, demonstrating its dynamic performance and reliability. Additionally, experimental results confirm the operational modes of the TPC topology and evaluate the behavior of the integrated PV and wireless battery system. This study highlights the advantages of an isolated power architecture, offering a robust and efficient solution for standalone applications.